Effect of air temperature and water depth on bird abundance: A case study of rallidae and anatidae in the northeastern Algerian Garaet Hadj Tahar - Bara, Mouslim (2019)
Water birds have traditionally been used as ecological indicators to monitor natural habitats and wetland changes. Climate is widely recognized as a major predictor of bird abundance and richness along large-scale environmental gradients, but mechanisms by which climate influences the bird abundance are still unknown. We analyzed seasonal variations on the bird community structure of Rallidae and Anatidae families in the northeastern Algerian Garaet Hadj Tahar for three consecutive years (September 2012 to August 2015). We studied the effect of air temperature and water depth on bird abundance and two ecological diversity indices (Shannon and Shannon E). Significant inter-annual fluctuations in bird abundance were recorded. Maximum values were always recorded during autumn. Water depth correlated positively with bird abundance and Shannon index. Field samplings indicated that bird abundance was frequently higher than 1000 individuals, which suggests that this site is an important refuge of water birds in the Guerbes-Sanhadja wetlands complex. Two key conservation species were observed regularly in the Garaet: near threatened Ferruginous Duck (Aythya nyroca) and endangered White-headed Duck (Oxyura leucocephala). Our results highlight the importance of preserving the Garaet Hadj Tahar as a water bird refuge.